The design and evaluation of "short-sighted" stochastic optimal controllers - Kleynhans, Bernardus Gerhard (Department of Electrical Engineering, 2016)
The quality of control provided by what is termed "short-sighted" stochastic optimal controllers controlling a linear heating system subjected to a random disturbance is evaluated by computer simulation and by experimentation.